Pediatric focally pigmented choroidal melanoma: Imaging with pathological correlation - Galluzzi, Paolo; Occhini, Rossella; Cerase, Alfonso; Toti, Paolo; Hadjistilianou, Theodora; Venturi, Carlo; Francesco, Sonia De (Journal of Pediatric Neuroradiology, 2013)
We report a 9-year-old-boy with no predisposing factors who presented with left eye leukocoria from a complete retinal detachment at ophthalmoscopy. Imaging showed an intraocular dome-shaped mass of low to moderate internal reflectivity at ultrasound, low T2-weighted signal intensity, lack of T1-weighted high signal intensity, and subtle gadolinium-enhancement at magnetic resonance imaging, and lack of calcifications at computed tomography. Due to the rapid extensive intraocular growth, the affected eye was enucleated. Pathologic examination showed a choroidal melanoma with only focal pigmentation. Despite its very rare incidence in the pediatric population, choroidal melanoma should be included in the differential diagnosis of leukocoria.
Keywords: Choroidal malignant melanoma; computed tomography; focal pigmentation; magnetic resonance imaging; pediatric ocular malignancy